2012
DOI: 10.1111/j.1442-9993.2011.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of plants, reptiles and birds to grazing management, fertilizer and tree clearing

Abstract: The relative effects of tree clearing, increased livestock densities and nutrient enrichment have rarely been compared across markedly different organism types, but negative effects are generally predicted. In contrast, adoption of rotational grazing is thought to benefit biodiversity in pastures but there are few supporting data. We examined the response of native plants, birds and reptiles to livestock management in south-eastern Australia. We selected 12 pairs of rotationally and continuously grazed farms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 48 publications
0
58
0
Order By: Relevance
“…We found tree cover and litter were positively associated with reptile abundance across the landscape and with species richness in paddocks. Tree presence and cover can affect reptile abundance and richness (Dorrough et al 2012;Michael et al 2015), and both leaf litter and rocks are important habitat features for many reptiles in this study (Michael et al 2015). Vegetation structure and cover is likely to influence the microclimate and therefore influence reptile thermoregulation (e.g.…”
Section: The Influence Of Remnant Patches and Other Vegetation Characmentioning
confidence: 99%
See 1 more Smart Citation
“…We found tree cover and litter were positively associated with reptile abundance across the landscape and with species richness in paddocks. Tree presence and cover can affect reptile abundance and richness (Dorrough et al 2012;Michael et al 2015), and both leaf litter and rocks are important habitat features for many reptiles in this study (Michael et al 2015). Vegetation structure and cover is likely to influence the microclimate and therefore influence reptile thermoregulation (e.g.…”
Section: The Influence Of Remnant Patches and Other Vegetation Characmentioning
confidence: 99%
“…Rotational grazing regimes can result in increased natural tree regeneration (Fischer et al 2009) although some studies have found no difference in vegetation structure between grazing regimes (e.g. Dorrough et al 2012). …”
Section: Grazing Regimesmentioning
confidence: 99%
“…Secondly, it provides a unique opportunity to assess the role of grazing in a system less likely to be confounded by evolutionary changes in plant communities in response to livestock grazing (Dorrough et al. ). In contrast to other continents, Australia has a very short history of grazing by European domestic livestock (<200 yr; Lunt et al.…”
Section: Introductionmentioning
confidence: 99%
“…First we assessed the evidence supporting the hypothesis that the effects of aridity varied according to one or more of the land cover or land use variables. We separately fitted each potential interaction between the climate and land cover or land use fixed effects and estimated the changes in the Akaike Land cover Canopy cover (0-100 %) Clearing native trees and shrubs impacts biodiversity (Dorrough et al 2012) Bare ground (0-100 %) Increased land use intensity (grazing and farming) reduces native plant groundcover and litter and increases bare soil cover affecting ground-active invertebrate biodiversity (Bromham et al 1999) Land use Land use intensity (Integers 0-12 converted to a proportion)…”
Section: Ant Community Structurementioning
confidence: 99%